OPTIMIZATION OF ISOFLAVONES PRODUCTION ON CALLUS (Pachyrhyzus et al.) THROUGH VARIATIONS IN SOURCES AND AMOUNT OF PLANTING MATERIAL - Indarwati, Indarwati; Herawati, Jajuk; Soeryaningsih, Dwie Retna; Widya, Surya Ari; Hassan, Faez M. (Yayasan Education and Social Center, 2024)
In vitro, biotechnology has proven to be a reliable source for producing secondary metabolites. Isoflavones are secondary plant metabolites that have antioxidant and estrogenic properties in the body. Tissue culture technology, which allows the production of plantlets or calluses in small containers, can address challenges in plant metabolite production. To enhance the efficiency of callus production, variations in sources and amount of planting material should be tested in a single planting container. The Bengkoang plant / Jicama (Pachyrhizus erosus) naturally produces isoflavones. This study investigates the impact of variations in sources and amount of planting material on the production of isoflavones in Bengkoang callus using in vitro tissue culture techniques. The research was conducted at the Tissue Culture Laboratory, employing a Completely Randomized Design (CRD) factorial method. Factor I involved the explant source: C1: young leaves; C2: Callus. Factor II involved the number of explants per container: T1: 1; T2: 2; T3: 3. The results show an interaction between source variations and the amount of planting material in anthocyanin production, successfully extracted from the Callus. Planting 3 explants in a container with subculture material from Callus produced the highest 0.16% isoflavones compared to other treatments